miR-379-5p retards the proliferation and differentiation of goat skeletal muscle satellite cells by targeting LIN28B - Hou, Wenyue; Huang, Shiyu; Zhao, Zihao; Xu, Xiaoli; Zhang, Hongping; Guo, Jiazhong; Cao, Jiaxue; Dai, Dinghui; Li, Li (Frontiers in Veterinary Science, 2025)
MicroRNAs (miRNAs) are emerging as crucial regulators of skeletal muscle development and regeneration; however, the biological functions of many miRNAs remain to be elucidated. In this study, we focused on the function of miR-379-5p, a miRNA we previously identified as highly expressed in the longissimus dorsi muscle of goats. Overexpression of miR-379-5p inhibited the proliferation and differentiation of goat skeletal muscle satellite cells (MuSCs), as evidenced by decreased expression of proliferation and differentiation markers, reduced EdU+ cells, and lower myotube formation. Through bioinformatics prediction and experimental validation, we identified LIN28B as a direct downstream target of miR-379-5p. Functional assays revealed that LIN28B promoted the proliferation and differentiation of MuSCs, whereas miR-379-5p suppressed these processes by decreasing LIN28B expression. Furthermore, miR-379-5p inhibited mitochondrial activity during the proliferation phase but promoted it during myogenic differentiation. Additionally, ectopic expression of LIN28B decreased mitochondrial membrane potential and enhanced reactive oxygen species (ROS) production, suggesting that LIN28B impairs mitochondrial function. Overall, our findings highlight the role of miR-379-5p and LIN28B in regulating goat MuSCs activity and mitochondrial function, providing new insights into the role of miRNAs in skeletal muscle development.